SCAPS simulation of ZnO/CdS/CdTe/CuO heterostructure for photovoltaic application - Zapukhlyak, Z. R.; Nykyruy , L.I.; Wisz, G.; Rubish, V.M.; Prokopiv, V.V.; Halushchak, M.O.; Lishchynskyy, I.M.; Katanova, L.O.; Yavorskyi , R.S. (Physics and Chemistry of Solid State, 2020)
The authors have developed a simple, cheap and reproducible technology for obtaining thin-film heterostructures based on CdTe with a given surface morphology during vacuum deposition, which contributes to their low cost [1, 2]. The critical dimensions (thicknesses) of individual layers of the heterostructure were substantiated, a simulation was performed and a wide range of optical properties was investigated [3]. It is shown that for the deposited CdS / CdTe heterostructure on glass it is possible to obtain an efficiency of 15.8%. Given that thin films are relatively new systems, their study can offer much wider opportunities for technological improvement of photovoltaic energy converters. According to the analysis of modern literature data, the efficiency can be increased by performing deposition on ITO films and introducing nanoparticles of controlled sizes.